Pengaruh peralihan kekuasaan industri rokok di Kudus hingga modernisasi industri rokok Kudus Tahun 1918-1964 - Naufal Mubarok Akhmad; Yuliati Yuliati (Universitas Negeri Malang, 2022)
The cigarette industry cannot be separated from the Kudus City which has been maintained since ancient times until now which has succeeded in prospering most of the people of Kudus City. The development of urban planning and supporting infrastructure in Kudus City, which is classified as very good, cannot be separated from the presence of the cigarette industry. Although there are many recommendations that smoking is prohibited because of its very bad impact on health, on the other hand, it is the situation of the cigarette industry that has moved the economy from the smallest sector, namely society, to the largest sector, namely the state. The author's purpose of discussing this is to introduce the history and dynamics of the cigarette industry in Kudus City so that it is successful for the welfare of the community, especially for the workers. This study uses the historical method in which observations are made through the results of the construction of past events to strengthen their conclusions from all kinds of observational sources. The results of the research are then used as a written paper as a reference for new learning sciences, especially regarding the cigarette industry. Industri rokok tidak bisa dipisahkan dengan Kota Kudus yang telah terjaga sejak dulu kala hingga sekarang ini yang telah berhasil menyejahterakan sebagian besar masyarakat Kota Kudus. Pembangunan tata kota dan infrastruktur pendukung di Kota Kudus yang tergolong sangat baik juga tidak terlepas karena hadirnya industri rokok. Walaupun banyak anjuran dilarang merokok karena dampaknya yang sangat buruk bagi kesehatan tetapi di lain situasi industri rokok inilah yang telah menggerakan perekonomian dari sektor terkecil yaitu masyarakat sampai sektor terbesar yaitu negara. Tujuan penulis membahas ini adalah untuk mengenalkan sejarah dan dinamika industri rokok di Kota Kudus hingga berhasil menyejahterakan masyarakat terutama bagi para buruhnya. Penelitian ini menggunakan metode historis dimana pengamatannya melalui hasil dari konstruksi peristiwa masa lalu untuk dikuatkan kesimpulannya dari segala macam sumber pengamatan. Hasil penelitian kemudian dijadikan suatu karya tulis sebagai referensi ilmu pembelajaran yang baru terutama mengenai industri rokok.